Labeling dan Pemanfaatan Instagram Pada Usaha Kerupuk Jamur Tiram - Rinartha, Komang; Kusuma, Tubagus Mahendra; Kartika, Luh Gede Surya (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Oyster mushroom is one of the edible mushrooms. Processed mushrooms in the form of crackers were chosen by partners because there are many in the market that process oyster mushrooms into Crispy Mushrooms. Thus, it is necessary to innovate mushroom-based foods in order to be able to compete in the market. Oyster mushroom crackers produced by partners do not yet have a product name and do not include a label containing the identity of the product. The oyster mushroom crackers are usually marketed on a limited basis by leaving them in stalls around the house or through limited orders. These oyster mushroom crackers are not yet widely known because there is no means of promotion used by partners to introduce their oyster mushroom crackers. Service activities begin with conducting a needs analysis of partner activities in the business of selling oyster mushrooms, providing understanding to partners through counseling / socialization of the importance of having a label as an identity so that it can be identified by consumers. The community service activity is also continued by providing counseling/socialization about online promotion for a small business and then partners will be accompanied in creating an Instagram account as a promotional medium.